Daily activity patterns in older adults receiving initial support: the association between daily steps and sitting in bouts of at least 60 min - Joakim Niklasson; Cecilia Fagerström; Sofia Backåberg; Terese Lindberg; Patrick Bergman (BMC Geriatrics, 2024)
Abstract Background Aging has a significant impact on health, underlining the importance of maintaining physical function and reducing time spent sitting among older adults. To understand how to reduce prolonged sitting or increase physical activity, factors related to the daily living and observed daily activity patterns should be explored. This study aimed to investigate the association between daily steps, self-rated health, physical activity, sedentary behavior, motivation to exercise and fear of falling among older adults receiving initial support. Method Cross-sectional design with total population questionnaire data from adults aged ≥ 60 years (n = 917), living at home with initial support from municipal care in southern Sweden. The older adults were offered to participate in a follow-up study measuring daily activity patterns with accelerometers (n = 72). Linear regression was used to analyze associations between daily steps and possible predictors. Results The linear model ( $$ R^{2}= $$ 0.478) showed that sitting in unbroken bouts of > 60 min (β = -0.313, p < 0.05), walking independently outdoors (β = 0.301, p < 0.05), intending to increase physical activity (β = -0.294, p < 0.05), sex (β = 0.279, p < 0.05), relative autonomy index (β = 0.258, p < 0.05), fear of falling (β = -0.238, p < 0.05), and self-rated health (β = 0.213, p < 0.05) predicted daily steps. Conclusion The model of predictors brings new understanding regarding daily steps among community-dwelling older adults. The association between sitting in bouts of > 60 min and daily steps is interesting as 35% of participants had a number of sitting bouts that on average, showed 30% less steps taken. Minimizing long sitting bouts and maintaining physical functioning to promote independence when walking outdoors can be tools for clinical practitioners devising interventions to break prolonged sitting among community-dwelling older adults. Future research should prioritize studying older adults’ outdoor walking independence, including its relation to walking with or without assistive devices and its impact on physical activity and sedentary behavior.